Evaluation the effect of burning investment and black sand materials on the surface roughness of acrylic resin denture base - jaber, Makarem (Iraqi National Journal of Nursing Specialties, 2012)
Objective: The aim of this study was to evaluate the effect of pumice, burning investment materialand black sand on the surface roughness of heat cure acrylic resin.Methodology: Sixty specimens were prepared from pink heat cure acrylic resin, the specimenswhere grouped into; 20 specimens which polished with pumice and water (control group); 20specimens which polished with investment material (after burning it) and water; and 20 specimenswhich polished with black sand and water. The average surface roughness of specimens afterpolishing procedure had been determined by profilometer (surface roughness tester).Results: Through the application of ANOVA and LSD tests, the result of this study showed that therewas a highly significant difference among the three groups at (P